An Easy and Rapid Spectrophotometric Method for Determination of Chloroquine Diphosphate in Tablets - Castro e Souza, Mateus Araújo; Reis, Naialy Fernandes Araújo; de Souza Batista, Larissa; da Costa César, Isabela; Fernandes, Christian; Pianetti, Gerson Antônio (Current Pharmaceutical Analysis, 2020)
Introduction: Malaria, an infectious disease caused by protozoa of the genus Plasmodium, is highly prevalent in the Brazilian Amazon. Chloroquine is the first-choice drug for the treatment of malaria caused by P. vivax and P. malariae. The humid and hot climate characteristic of the Brazilian endemic region favors drug degradation and modification of its biopharmaceutical properties, which may result in subtherapeutic dosage, formation of degradation products that can be toxic to humans and appearance of parasitic resistance. Thus, it is necessary to monitor the quality of chloroquine tablets. Materials and Methods: An analytical method was developed and validated to determine chloroquine content in tablets by ultraviolet spectrophotometry. The diluent consisted of 0.06 M monosodium phosphate buffer pH 6.8 and detection was performed at 343 nm. Results and Conclusion: The method proved to be linear in the range of 7.2 to 19.2 μg.mL-1, precise, accurate, selective, robust, and statistically equivalent to a liquid chromatographic method by the United States Pharmacopeia. The developed method was applied to determine chloroquine content in six batches of the drug. The evaluated batches were considered adequate for identification, assay, dissolution, disintegration and uniformity of dosage units, and were found to be inadequate in terms of friability.
Keywords: tablets